Early Vascular Aging in Children With Type 1 Diabetes and Ambulatory Normotension - Šuláková, Terezie; Strnadel, Jiří; Pavlíček, Jan; Poláková, Radka; Seeman, Tomáš; Feber, Janusz (Frontiers in Pediatrics, 2021)
Background: Preliminary data suggests that target organ damage (TOD) and early vascular aging (EVA) may occur in children with normal blood pressure (BP). Objectives: To analyze TOD and EVA in normotensive (BP <95th percentile on ambulatory BP monitoring) type 1-diabetes children (T1D) in comparison to healthy controls (C). Subjects: 25 T1D aged 13.9±2.6 yrs. and 22 C aged 14.0±3.4 yrs. Methods: We analyzed age- and height related pulse wave velocity (PWV) Z-scores and expected PWV based on age, height and MAP. Expected vascular age based on measured PWV was calculated from pooled pediatric and adult PWV norms. Left ventricular mass index (LVMI), eGFR, and urinary albumin/creatinine ratio (ACR) were obtained as markers of TOD. Results: T1D and C groups did not differ in anthropometry, ambulatory, LVMI and ACR. However, medians age- and height-related PWV Z-scores were higher in T1D compared to C (1.08 vs 0.57, p=0.006; 0.78 and 0.36, p=0.02, respectively). Mean (±SD) difference between measured and expected PWV was 0.58 ± 0.57 in T1D vs 0.22 ± 0.59 in C, p=0.02. The mean (±SD) difference between chronological and expected vascular age was 7.53 ± 7.74 years in T1D vs 2.78 ± 7.01 years in C, p=0.04. Conclusion: Increased arterial stiffness and increased intraindividual differences between expected and measured PWV as well as between chronological and expected vascular age indicate that early vascular aging (EVA) may develop in T1D children even at normal ambulatory BP levels.